Urea-Based Synthesis of Zinc Oxide Nanostructures at Low Temperature. (14th May 2012) - Marinho, J. Z.; Romeiro, F. C.; Lemos, S. C. S.; Motta, F. V.; Riccardi, C. S.; Li, M. S.; Longo, E.; Lima, R. C.
Abstract : The preparation of nanometer-sized structures of zinc oxide (ZnO) from zinc acetate and urea as raw materials was performed using conventional water bath heating and a microwave hydrothermal (MH) method in an aqueous solution. The oxide formation is controlled by decomposition of the added urea in the sealed autoclave. The influence of urea and the synthesis method on the final product formation are discussed. Broadband photoluminescence (PL) behavior in visible-range spectra was observed with a maximum peak centered in the green region which was attributed to different defects and the structural changes involved with ZnO crystals which were produced during the nucleation process.